Identifikasi faktor protektif dan resiko pada siswa di Kota Jambi - Fadzlul Fadzlul; Nofrans Eka Saputra; Yun Nina Ekawati; Jelpa Periantalo (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Risk behaviors are behaviors associated with health problems. The health problems including infectious diseases, HIV problem even AIDS, chronic diseases, psychosomatic disorder, substance addiction, use of illegal drugs, drinking, and psychological disorders. Protective and risk factors is an ability that is expected to be owned by everyone. METHOD This study aims to difference of protective and risk factors based school. The study population was taken with purposive random sampling technique, the characteristics of which students (including smokers, active sexual behavior, drug users) aged 12-21 years. The sample of this research were 518 responden. Analysis of the data will be used using varians analysis. RESULTS Results showed a difference between protective and risk factors based home school students with a p-value of 0.012. Junior high school students do not have a difference of protective and risk factors than high school students with a p-value 0.0947 , and junior high school students have a difference of protective and risk factors with vocational students with p value 0.022 . Junior high school students have a protective and risk factors a higher risk than vocational students . High school students have a difference of protective and risk factors with vocational students with p value 0.039 . High school students have the protective and risk factors a higher risk than vocational students . Vocational students have protective and risk factors is lower than high school students. CONCLUSIONS AND RECOMMENDATIONS Risk behavior has become a part of student life. Institutions in order to cooperate with relevant parties in structuring the activities in a sustainable manner in reducing risk behaviors in students. By conducting the preparation of the intervention module for dealing with problems in the risk behavior of students is expected to be a solution to reduce the number of occurrence of risk behavior.